Video-Based Learning (VBL): An Implementation on Advanced Learners of English Class - Abdul Haris Sunubi; Rustam Utary (ELITE JOURNAL, 2020)
As commonly known, the use of video in English Foreign Language (EFL) classrooms can facilitate the students to get more interested in learning and also enhance their communicative competences. This study aims to find out the effect of using video as teaching media in English class towards students’ achievement and obstacles in using it. It is designed in experimental study. The result of pre-test and post-test did not show significant differences although students’ scores increased. However, the result of observation showed students’ improvement in attitudes. They are motivated in learning through videos. They show positive attitudes although they undergo some obstacles in accessing the video outside the classroom namely internet-related problem such as sudden disconnected internet, running out internet data, as well as scheduled time for using handphone at school day. Besides, discussing the lesson from video in group chat of whatsapp is ineffective since they cannot follow the flow the information, since too many chats sent at the same time into group. However, the implementation of using video in this study can be implemented, since the learning activities were very enjoyable by using some techniques presented in this study.